Childhood Abuse History, Posttraumatic Stress Disorder, Postpartum Mental Health, and Bonding: A Prospective Cohort Study. (1st February 2013) - Seng, Julia S.; Sperlich, Mickey; Low, Lisa Kane; Ronis, David L.; Muzik, Maria; Liberzon, Israel
Abstract : Introduction: Research is needed that prospectively characterizes the intergenerational pattern of effects of childhood maltreatment and lifetime posttraumatic stress disorder (PTSD) on women's mental health in pregnancy and on postpartum mental health and bonding outcomes. This prospective study included 566 nulliparous women in 3 cohorts: PTSD‐positive, trauma‐exposed resilient, and not exposed to trauma. Methods: Trauma history, PTSD diagnosis, and depression diagnosis were ascertained using standardized telephone interviews with women who were pregnant at less than 28 gestational weeks. A 6‐week‐postpartum interview reassessed interim trauma, labor experience, PTSD, depression, and bonding outcomes. Results: Regression modeling indicates that posttraumatic stress in pregnancy, alone, or comorbid with depression is associated with postpartum depression ( R 2 = .204; P < .001). Postpartum depression alone or comorbid with posttraumatic stress was associated with impaired bonding ( R 2 = .195; P < .001). In both models, higher quality of life ratings in pregnancy were associated with better outcomes, while reported dissociation in labor was a risk for worse outcomes. The effect of a history of childhood maltreatment on both postpartum mental health and bonding outcomes was mediated by preexisting mental health status. Discussion: Pregnancy represents an opportune time to interrupt the pattern of intergenerational transmission of abuse and psychiatric vulnerability. Further dyadic research is warranted beyond 6 weeks postpartum. Trauma‐informed interventions for women who enter care with abuse‐related PTSD or depression should be developed and tested.